Performance and operational feasibility of antigen and antibody rapid diagnostic tests for COVID-19 in symptomatic and asymptomatic patients in Cameroon: a clinical, prospective, diagnostic accuracy study. Issue 8 (August 2021) - Boum, Yap; Fai, Karl Njuwa; Nikolay, Birgit; Mboringong, Akenji Blaise; Bebell, Lisa M; Ndifon, Mark; Abbah, Aristide; Essaka, Rachel; Eteki, Lucrèce; Luquero, Francisco; Langendorf, Céline; Mbarga, Nicole Fouda; et al.
Summary: Background: Real-time PCR is recommended to detect SARS-CoV-2 infection. However, PCR availability is restricted in most countries. Rapid diagnostic tests are considered acceptable alternatives, but data are lacking on their performance. We assessed the performance of four antibody-based rapid diagnostic tests and one antigen-based rapid diagnostic test for detecting SARS-CoV-2 infection in the community in Cameroon. Methods: In this clinical, prospective, diagnostic accuracy study, we enrolled individuals aged at least 21 years who were either symptomatic and suspected of having COVID-19 or asymptomatic and presented for screening. We tested peripheral blood for SARS-CoV-2 antibodies using the Innovita (Biological Technology; Beijing, China), Wondfo (Guangzhou Wondfo Biotech; Guangzhou, China), SD Biosensor (SD Biosensor; Gyeonggi-do, South Korea), and Runkun tests (Runkun Pharmaceutical; Hunan, China), and nasopharyngeal swabs for SARS-CoV-2 antigen using the SD Biosensor test. Antigen rapid diagnostic tests were compared with Abbott PCR testing (Abbott; Abbott Park, IL, USA), and antibody rapid diagnostic tests were compared with Biomerieux immunoassays (Biomerieux; Marcy l'Etoile, France). We retrospectively tested two diagnostic algorithms that incorporated rapid diagnostic tests for symptomatic and asymptomatic patients using simulation modelling. Findings: 1195 participants were enrolled in the study. 347 (29%) tested SARS-CoV-2 PCR-positive, 223 (19%) rapid diagnostic test antigen-positive, and 478 (40%) rapid diagnostic test antibody-positive. Antigen-based rapid diagnostic test sensitivity was 80·0% (95% CI 71·0–88·0) in the first 7 days after symptom onset, but antibody-based rapid diagnostic tests had only 26·8% sensitivity (18·3–36·8). Antibody rapid diagnostic test sensitivity increased to 76·4% (70·1–82·0) 14 days after symptom onset. Among asymptomatic participants, the sensitivity of antigen-based and antibody-based rapid diagnostic tests were 37·0% (27·0–48·0) and 50·7% (42·2–59·1), respectively. Cohen's κ showed substantial agreement between Wondfo antibody rapid diagnostic test and gold-standard ELISA (κ=0·76; sensitivity 0·98) and between Biosensor and ELISA (κ=0·60; sensitivity 0·94). Innovita (κ=0·47; sensitivity 0·93) and Runkun (κ=0·43; sensitivity 0·76) showed moderate agreement. An antigen-based retrospective algorithm applied to symptomatic patients showed 94·0% sensitivity and 91·0% specificity in the first 7 days after symptom onset. For asymptomatic participants, the algorithm showed a sensitivity of 34% (95% CI 23·0–44·0) and a specificity of 92·0% (88·0–96·0). Interpretation: Rapid diagnostic tests had good overall sensitivity for diagnosing SARS-CoV-2 infection. Rapid diagnostic tests could be incorporated into efficient testing algorithms as an alternative to PCR to decrease diagnostic delays and onward viral transmission. Funding: Médecins Sans Frontières WACA and Médecins Sans Frontières OCG. Translations: For the French and Spanish translations of the abstract see Supplementary Materials section.